Dismantling public policy preferences, strategies, and effects - Bauer, Michael W. (Oxford University Press, 2013)
'Dismantling Public Policy' seeks to develop a comparative approach to understanding policy dismantling. It looks at the cutting, reduction, diminution or complete removal of existing policies.